VALUES OF ISLAMIC EDUCATION IN FILM BILAL: A NEW BREED OF HERO BY AYMAN JAMAL - Amiruddin Siahaan; Mahmud Qazzan Zaki Sinaga (Universitas Dharmawangsa, 2020)
The study aims to find out how Islamic educational values are contained in the film Bilal: A New Breed of Hero. This type of research is a library of research with a semiotic approach. The semiotic approach is used to describe the content expressed or implied in the film. The method of data collection that researchers use is a method of documentation through the search of movie documents, newspapers, magazines, and books. Researchers use content analysis as a data analysis technique. The results of the study show the values of Islamic education contained in the film Bilal: A New Breed of Hero includes three things, the aqidah, worship and akhlaq. Starting from the value of aqidah that Bilal show through faith in Allah SWT and faith to Rasulullah SAW. The value of worship with charity and become Mu'adzin of Islam. While the akhlaq value among them is a moral to Allah SWT includes Taqwa. The personal morality includes help, patience, and forgiving. The moral